Study on the water–salt migration law of salinized frozen soil based on the capillary model - Bao, Dejun; Zhang, Zhilong; Yue, Zheng; Zhang, Ao; Liu, Guang (Frontiers in Earth Science, 2024)
Salt expansion and frost heave are the main diseases of salted frozen soil roadbeds. Salt swelling and frost heave disease are closely related to the salted soil water–salt migration, temperature variation, and salt crystallization amount change. This article establishes a coupled model of water, heat, and salt fields based on the capillary model and the unfrozen water characteristic curve. The study shows that the different initial moisture contents have minimal effects on the location of soil salt migration and aggregation. The different initial salt concentrations have a substantial effect on the soil water–salt migration aggregation position; when the concentration of sodium sulfate increases, different from chloride saline soils, the position of the freezing front fluctuates up and down over time. The water–salt migration and aggregation are smaller in the closed condition, where they are reduced by 38% and 20%, respectively.